Implikasi Putusan Mahkamah Agung Nomor: 3096 K/Pid.Sus/2018 Terhadap Jamaah First Travel - Muhamad Angga Ririhena; Teng Berlianty; Sabri Fataruba (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: This research is supported by the Supreme Court Decision Number 3096 K / Pid.Sus / 2018 which in its ruling ordered that First Travel's assets be confiscated and returned to the state treasury, even though the First Travel assets are not actually state assets, but originated from fraud to the First Travel congregation.Purposes of the Research: This study aims to study and analyze the consequences of the Supreme Court decision Number 3096 K / Pid.Sus / 2018 which are detrimental to Jamaah First Travel, and how civil law attempts are made.Methods of the Research: The type of research is juridical normative, while the nature of the research is descriptive analytical with two approaches, namely the statutory approach and the conceptual approach.Results of the Research: The results of the research show that the basis for the consideration of the Supreme Court Judges in the decision Number 3096 K / Pid.Sus / 2018 which considers that First Travel assets are considered as state assets and assets so that they must be confiscated and confiscated for the state is very wrong because the assets owned by First Travel are actually the result of fraud by the First Travel owner against the congregation, so that it must be returned to the First Travel congregation. The legal efforts that have been made by the First Travel congregation are suing the leadership of First Travel Andika Surachman as the Defendant and the Head of the Indonesian Attorney General and the Head of the Depok District Attorney as Co-Defendant and after going through a long trial process finally the Depok District Court, in this case the Panel of Judges who examined and adjudicated the case, decided that the lawsuit could not be accepted for all even though the Chief Judge made a dissenting opinion, on the verdict, the First Travel congregation actually could make an appeal to the High Court, but they did not do it because they had not. believe in the Court.